Concepts of “chaos” and “evil” correlation in history of philosophical thought - A V Kulik (RUDN Journal of Philosophy, 2014)
The examples of ethical interpretation of “chaos” by such philosophers as Plotinus, S. Kierkegaard, V. Soloviev, M. Scheler, N. Berdyaev are analyzed in the article. It is argued that all these interpretations demonstrate the connection between concepts of “chaos” and “evil”. It is proven that theories about ethical content of concept of “chaos” are based on ideas of God as the source of order.